De la noblesse médiévale à la noblesse moderne. La création dans les anciens Pays-Bas d'une noblesse dynastique (XVe-début XVIIe siècle) - Janssens, P. (BMGN - Low Countries Historical Review, 2008)
Nobility in the Low Countries from Medieval Times to the Modern Era. The Creation of a Dynastic Nobility (from the 15th to the 17th Century)In order to gain the allegiance of the major families during the creation of their new state in the Netherlands, the Burgundian dukes lavishly awarded the Order of the Golden Fleece. Charles V and Philip II, on the other hand, preferred to bestow an aristocratic title upon distinguished families from the Netherlands. Less eminent families were decorated with a lower noble rank or a knighthood. Up until the end of the 16th century, these lower level decorations tended to be given out sporadically. The princely patents of nobility made their breakthrough after 1595 thanks to the demise of the traditional form of acquiring a noble rank or knighthood by means of performing feudal duties. Henceforth, anyone who was decorated for a service to the sovereign could enter the ranks of the nobility. This is how a new nobility based on patents came into being, in which service to the monarchy was the deciding factor. This article is part of the special issue 'The history of the nobility in the Netherlands and Belgium'.